Designing Effective Mobile Health Apps: Does Combining Behavior Change Techniques Really Create Synergies?. Issue 2 (3rd April 2021) - Spohrer, Kai; Fallon, Monica; Hoehle, Hartmut; Heinzl, Armin
ABSTRACT: Although several theories could be applied to stimulate mobile health (mHealth) use and change people's health behaviors, theory-driven mHealth designs are scarce. Instead, developers and researchers often implement behavior change techniques and mix multiple techniques without explicitly considering their underlying theoretical mechanisms. We call this practice into question and propose that combining behavior change techniques does not necessarily result in synergistic effects. Drawing on theories of protection motivation and social upward comparison, we engage in explanatory design theorizing to understand interactions of behavior change techniques and their implications for mHealth design. We design, theorize about, and evaluate four mHealth prototypes for stress alleviation. In a five-week field experiment with n = 138 participants and a subsequent qualitative substantiation, we show that there is a negative interaction effect of protection motivation and social upward comparison, rendering their combined application less effective. Our findings elicit mutual boundary conditions for theories of protection motivation and social upward comparison. If mechanisms of one theory are present, they restrict the effectiveness of mechanisms of the other theory. Thus, mHealth developers need to use caution when combining different behavior change techniques within one mHealth artifact.